The Development and Clinical Application of Innovative Optical Ophthalmic Imaging Techniques - Alexopoulos, Palaiologos; Madu, Chisom; Wollstein, Gadi; Schuman, Joel S. (Frontiers in Medicine, 2022)
The field of ophthalmic imaging has grown substantially over the last years. Massive improvements in image processing and computer hardware have allowed the emergence of multiple imaging techniques of the eye that can transform patient care. The purpose of this review is to describe the most recent advances in eye imaging and explain how new technologies and imaging methods can be utilized in a clinical setting. The introduction of Optical Coherence Tomography (OCT) was a revolution in eye imaging and has since become the standard of care for a plethora of conditions. Its most recent iterations, OCT angiography and visible light OCT, as well as imaging modalities such as fluorescent lifetime imaging ophthalmoscopy, would allow a more thorough evaluation of patients and provide additional information on disease processes. Towards that goal, the application of adaptive optics and full-field scanning to a variety of eye imaging techniques has further allowed the histologic study of single cells in the retina and anterior segment. Towards the goal of remote eye care and more accessible eye imaging, methods such as handheld OCT devices and imaging through smartphones have emerged. Finally, incorporating artificial intelligence in eye images has the potential to become a new milestone for eye imaging while also contributing in social aspects of eye care.